Die Beurteilung der Wirksamkeit der BEMER-Therapie bei der körperlichen Regeneration nach dem Ausdauertraining. Case study = The evaluation of the efficacy of BEMER therapy in the physical recovery after endurance training. Case study - Mirosław Mrozkowiak (Kazimierz Wielki University, 2016)
Mrozkowiak Mirosław. Die Beurteilung der Wirksamkeit der BEMER-Therapie bei der körperlichen Regeneration nach dem Ausdauertraining. Case study = The evaluation of the efficacy of BEMER therapy in the physical recovery after endurance training. Case study. Journal of Education, Health and Sport. 2016;6(4):399-428. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50580 http://ojs.ukw.edu.pl/index.php/johs/article/view/3493   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.04.2016. Revised 25.04.2016. Accepted: 27.04.2016.   Die Beurteilung der Wirksamkeit der BEMER-Therapie bei der körperlichen Regeneration nach dem Ausdauertraining. Case study The evaluation of the efficacy of BEMER therapy in the physical recovery after endurance training. Case study   Mirosław Mrozkowiak   Bioergonsport, Nowa Biała 8p, 09-411 Biała       dr Mirosław Mrozkowiak Bioergonsport, Nowa Biała 8p, 09-411 Biała   Key words: BEMER therapy. Schlüsselwörter: BEMER-Therapie.   Abstract   The method used and Signaling - BEMER affects the values of selected blood parameters: heart rate, systolic and diastolic pressure, and oxygen saturation. The BEMER therapy in biologic regeneration after physical regeneration for men in 5-6 decade of life may be justified. Further investigations regarding the application of BEMER stimulation in biological regeneration should be on the impact on the restitution to the physical nature of appropriate human, age and gender groups, directed. When planning studies is the year and day, and to be considered in the women's menstrual phase in the cycle. Regarding the adopted organization of studies, there were no allegations. The standard is intended to effort rather towards a permanent rather Interval load be modified. Because no significant changes to Bioelectromagnetic stimulation to templates to dispense with WBC, PCO2, cHCO3 and recognition functions and selected urea parameters at this point: analyze sodium, potassium, hemoglobinuria, chlorides, sulfates, ammonia, nitrogen and creatine.       Abstrakt   Die angewendete Methode und Signaltechnik - BEMER beeinflusst die Werte ausgewählter Blutparameter: Puls, systolischer und diastolischer Druck und Sauerstoffsättigung. Der Einsatz der BEMER Therapie in der bioliogischen Regeneration nach der körperlichen Regeneration bei den Männern im 5-6 Lebensjahrzehnt kann begründet sein. Die weiteren Untersuchungen bezüglich der Anwendung der BEMER-Stimulierung in der biologischen Regeneration sollen auf den Einfluss auf die Restitution nach der körperlichen Anstrengung bei entsprechenden Menschen-, Alters- und Geschlechtsgruppen, gerichtet werden. Bei der Planung von Untersuchungen ist die Jahres- und Tageszeit und bei den Frauen die Menstruationsphase im Zyklus, zu berücksichtigen. Bezüglich der angenommenen Organisation der Untersuchungen gab es keinerlei Vorwürfe. Die Standardanstrengung soll dabei eher Richtung einer ständigen und nicht Intervalbelastung modifiziert werden. Weil keine wesentlichen Änderungen nach bioelektromagnetischen Stimulierung vorlagen soll auf WBC, PCO2, cHCO3 und Erkennungsfunktionen verzichtet werden und an dieser Stelle ausgewählte Harnstoffparameter: Natrium, Kalium, Hämoglobinurie, Chloride, Sulfate Ammoniak, Stickstoff und Kreatin analysieren.